Penggunaan Model Pembelajaran Project Based Learning (PjBL) untuk Meningkatkan Kemampuan dan Motivasi Siswa - Qalbina, Putri; Melta, Defrian; Asrizal, Asrizal; Desnita, Desnita; Diliarosta, Skunda (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2023)
In science learning, it is necessary to emphasize learning that refers to direct experience so that it can provide space for students to develop the ability to think, work and act scientifically in an integrated manner. The problem found at this time is the lack of motivation in students so that it has an impact on learning outcomes. One solution to overcome these problems is to use a learning model that can improve students' abilities and motivation. The PjBL model provides opportunities for teachers to manage learning in class by involving project work (activities), so students will be trained to have good thinking skills and generate motivation in students. This study aims to examine the use of project based learning learning models in science learning to improve students' abilities and motivation. The research method used is systematic literature review. The data used in this study were obtained from previous research, in the form of articles related to the Project Based Learning learning model. The results of the research by analyzing several articles show that the use of the Project Based Learning learning model in science learning can improve students' abilities and motivation in learning.